Paediatric refugees from Ukraine: guidance for health care providers (Swiss Medical Weekly, 2022)
BACKGROUND: With the invasion of Ukraine by the Russian Army in February 2022, refugees, the majority of whom are women and children, started fleeing the war to neighbouring countries. Even before the current escalation, the conflict in the eastern part of Ukraine has led to the internal displacement of more than 200,000 children, and many others have experienced attacks, e.g. on schools. This inevitably leads to limitations in health care delivery. During transit, overcrowding, poor shelter and vulnerability may further put refugees at increased risk for infectious diseases. This consensus document aims to provide information and guidance regarding health issues that paediatricians and general practitioners may face when caring for Ukrainian children.METHODS: Members of the Migrant Health Reference Group of Paediatrics Switzerland and the Paediatric Infectious Disease Group in Switzerland developed this recommendation between March and April 2022 in a modified Delphi process.RESULTS: A total of 50 recommendations were agreed on with a ≥80% consensus. These include the following topics: i) general aspects, including interpreter services, urgent health needs, personal history and general check-ups; ii) mental health, including how to search for signs of psychological distress without going into traumatic details; iii) vaccinations, including recommendations for evaluation and catch-up; iv) screening for tuberculosis, human immunodeficiency virus, and hepatitis B and C; and v) providing age-appropriate preventive and health service information.CONCLUSION: This document provides current evidence and guidance when caring for paediatric refugees from Ukraine. The recommendations focus on Switzerland but may well be used in other countries. These are based on current evidence and may need to be adapted to individual situations and once further evidence becomes available.